Fatores prognósticos dos pacientes com esclerose mesial temporal submetidos à corticoamigdalohipocampectomia em centro terciário - Adry, Rodrigo Antonio Rocha da Cruz (2017)
Mesial temporal sclerosis (MTS) is the most common disease encountered in an epilepsy surgery series. Early age of onset, a history of febrile convulsions, epileptiform discharges on EEG, duration of epilepsy, number of generalized seizures, type of auras and severity of psychiatric disorders are possible prognostic factors in patients with MTS. Objetive: The aim of this study is to assess the results of clinical research, semiotic, psychological, electrophysiological and neuroradiological, associating their findings with the prognosis of patients with MTS who underwent cortico-amygdalohippocampectomy (CAH). Methods: Of 1214 patients evaluated for surgery in the Epilepsy Center of Faculdade de Medicina de São Jose do Rio Preto (FAMERP), a tertiary brazilian epilepsy center, 400 underwent CAH for MTS. Exams and clinical data were analyzed and compared with Engel classification for outcome. Results: Of all the items analyzed, the MRI showed a greater influence on the outcome of patients and for clinical evaluation and pathological antecedents, age at surgery, the epilepsy duration, perinatal insults, a family history of epilepsy, febrile seizures, neuropsychological abnormalities and presence of generalized tonic clonic seizure had a statistical significance. A significant relationship was found between the side of MTS under MRI and on SPECT with bilateral ictal EEG showing worse results. Surgical results correlated with ictal and interictal scalp EEG patterns and there was no difference when analyzing unilateral or bilateral discharges regardless of whether it was the interictal or ictal EEG. Analyzing the patients according to the type of aura, those who had extratemporal auras had worst result in post-surgical in Engel classifcation. While mesial auras apparently are a good prognostic factor. Patients without aura also had worse prognosis. Simple and multiple aura had no difference. Conclusion: In order to identify the most appropriate candidates for CAH, it is very important to consider the prognostic factors associated with favorable result for counseling these patients in daily practice.